Local Frequency Table for Context-based Adaptive Arithmetic Coding in Text Compression - Tsai, Yi-Lin; Ding, Jian-Jiun (IEEE International Conference on Consumer Electronics-China (Online), 2022)
Adaptive arithmetic coding is widely adopted in text compression. However, to achieve a high coding gain, an advanced way for context assignment is required. In this paper, the local frequency table technique is adopted to improve the coding efficiency of context-based adaptive arithmetic coding in text compression. With it, the probability distribution of the characters to be encoded can be estimated more accurately and a higher compression ratio can be achieved. Experimental results show that the proposed coding algorithm with a local frequency table outperforms other methods and achieves better compression performance for text compression.